Alpha7 Nicotinic Acetylcholine Receptor Down Regulation Impairs Mitochondrial Function in Streptozotocin-induced Sporadic Alzheimer's Disease Model in Rats - Singh, Niraj Kumar; Garabadu, Debapriya (Indian Journal of Pharmaceutical Education and Research, 2021)
Background/Aim: Alzheimer’s disease (AD), a type of neurodegenerative disorder, possesses significant memory loss as one of the cardinal manifestations. The pathophysiology of AD includes increased accumulation of Aβ, degeneration of cholinergic activity and mitochondrial dysfunction. Nicotinic acetylcholine receptors (nAChRs) especially alpha7 nicotinic acetylcholine receptors (α7 nAChRs) are widely distributed in brain and associated with memory function. Further, we explored the correlation between the mitochondrial dysfunction and the expression level of α7 nAChRs in STZ challenged brain regions of rats. Materials and Methods: The STZ group rats received intracerebroventricular infusion of STZ (3 mg/kg) on D-1 and D-3 of experimental design of 18 days. Behavioral parameters ware investigated using MWM and Y-maze test paradigm. Further, biochemical analysis was assessed in all three regions of rats. Results: STZ administration caused significant impairment in memory and learning of rats MWM and Y-maze test paradigm. There was significant decrease in level expression of α7 nAChRs and cholinergic functions in terms of elevated AChE activity and decreased ACh level and ChAT activity in rat hippocampus, pre-frontal cortex and amygdala. Further, STZ administration significantly attenuated the mitochondrial function, integrity and bioenergetics in all the selected brain regions. Interestingly, the intracerebroventricular infusion of STZ increased Aβ level in all the rat brain regions. Conclusion: The α7 nAChR down regulation may form a basis to cognitive deficits along with cholinergic dysfunction, Aβ accumulation and mitochondrial dysfunction in memory sensitive rat brain regions. Thus, α7 nAChR could be an alternative and potential target in the management of AD.
Keywords: Alzheimer’s disease; Streptozotocin; α7 nAChR; Mitochondria; Acetylcholine; Hippocampus